2002
DOI: 10.1105/tpc.004838
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cell Cycle Distribution, Hyperplasia, and Inhibited Differentiation in Arabidopsis Caused by the D-Type Cyclin CYCD3

Abstract: CYCD3;1 expression in Arabidopsis is associated with proliferating tissues such as meristems and developing leaves but not with differentiated tissues. Constitutive overexpression of CYCD3;1 increases CYCD3;1-associated kinase activity and reduces the proportion of cells in the G1-phase of the cell cycle. Moreover, CYCD3;1 overexpression leads to striking alterations in development. Leaf architecture in overexpressing plants is altered radically, with a failure to develop distinct spongy and palisade mesophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
333
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(363 citation statements)
references
References 46 publications
29
333
0
1
Order By: Relevance
“…For example, expression of a dominant-negative Arabidopsis CDKA in transgenic tobacco results in almost normal-sized leaves with fewer but larger cells (Hemerly et al, 1995). In Arabidopsis, overexpression of CycD3;1 , a G1 cyclin gene, does not increase organ size but leads to a disturbed organogenesis, with numerous small, incompletely differentiated cells (Riou-Khamlichi et al, 1999;Dewitte et al, 2003). Similar data were obtained from overexpression of E2Fa and DPa, two transcriptional factors that play a role in activating cell division genes.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, expression of a dominant-negative Arabidopsis CDKA in transgenic tobacco results in almost normal-sized leaves with fewer but larger cells (Hemerly et al, 1995). In Arabidopsis, overexpression of CycD3;1 , a G1 cyclin gene, does not increase organ size but leads to a disturbed organogenesis, with numerous small, incompletely differentiated cells (Riou-Khamlichi et al, 1999;Dewitte et al, 2003). Similar data were obtained from overexpression of E2Fa and DPa, two transcriptional factors that play a role in activating cell division genes.…”
Section: Introductionmentioning
confidence: 63%
“…CycD3;1 expression suggested that CycD3;1 acts downstream of ANT to determine leaf cell number (Dewitte et al, 2003). Most importantly, the prolonged expression of ANT is observed in fully expanded 35S-ARGOS leaves, and the loss of function of ANT blocked organ enlargement in 35S-ARGOS plants.…”
Section: Argos or Ant A Recent Study Of Transgenic Plants With Ectopicmentioning
confidence: 99%
“…In these plants, cell cycle progression was limited and the uncoupling of cell growth from cell division resulted in an increase of the final cell size (De Veylder et al, 2001). By contrast, constitutive overexpression of the D-type cyclin CYCD3 (Dewitte et al, 2003) and the cell cycle-regulating transcription factors E2Fa and DPa (De Veylder et al, 2002) was shown to cause the hyperproliferation of smaller and incompletely differentiated leaf cells. These comparisons indicate that the altered leaf phenotype of AtCKX transgenic plants could be achieved through the regulation of cell cycle genes.…”
Section: Cytokinin Controls the Frequency Of Leaf Initiation And Leafmentioning
confidence: 99%
“…11 It has been shown that sucrose and hormone concentrations in tissue culture medium are perceived by CycD3;1/CDK in Arabidopsis, which are upregulated. 12 In tobacco cell culture, upregulation of CycD3;1 stimulates cell proliferation by the direct inhibition of RBR. 13 Thus, evidence from two readily transformable dicot species with a single RBR gene suggests that inactivation of RBR through phosphorylation by CycD/CDK may be sufficient to relieve the RBR cell cycle block.…”
mentioning
confidence: 99%